Harmoni Ekologis dalam Petuah Adat Sikka dan Lamalera: Pedoman Hidup di Tengah Tantangan Modern - Christian Wildeciano Jogo; Marselinus Kalang Lelaona; Kasimirus Rape Baluk (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2026)
This research analyzes the noble values of the Sikka and Lamalera communities contained within the customary advice, "Hode Lau Ina Limé, Ina Soro Sare-Sare" (Lamalera – Lembata) and "Blatang Ganu Wair, Blirang Ganu Wolong/Bao" (Sikka, Maumere). Both pieces of advice are inherited from ancestors, serve as the foundation for the formation of local culture, and reflect a harmonious relationship between humans and nature with an emphasis on the ecological aspect.They illustrate how nature, encompassing both the sea and the land with its environment, is viewed not merely as a resource but also as a sacred entity that must be respected. Amidst rapid modernization, the appreciation for tradition and customary advice is increasingly marginalized, and the articulation of the noble values of the surrounding environment is often neglected.The main challenge lies in how these noble values can serve as an effective guide for life in maintaining environmental balance and harmony amid the challenges of modern development, and how to prevent the destruction of the harmonious relationship between humans and nature as attention to tradition diminishes. The research methodology is descriptive qualitative with an analytical approach, utilizing interviews and literature review for data collection. Findings indicate that the noble values of the environment represent the embodiment of the Creator's presence, who sustains and maintains the community's survival.AbstrakPenelitian ini menganalisis nilai-nilai luhur masyarakat Sikka dan Lamalera yang terkandung dalam petuah adat "Hode Lau Ina Limé, Ina Soro Sare-Sare" (Lamalera – Lembata) dan "Blatang Ganu Wair, Blirang Ganu Wolong/Bao" (Sikka, Maumere). Kedua petuah ini diwariskan nenek moyang dan berfungsi sebagai latar belakang terbentuknya kebudayaan lokal, serta mencerminkan hubungan harmonis antara manusia dan alam dengan penekanan pada aspek ekologis. Keduanya menggambarkan bagaimana alam, baik laut maupun daratan dengan lingkungannya, tidak hanya dipandang sebagai sumber daya, tetapi juga sebagai entitas suci yang harus dihormati. Di tengah pesatnya perkembangan zaman, penghayatan terhadap tradisi dan petuah adat kian terpinggirkan, dan pengungkapan nilai luhur alam sekitar sering kali diabaikan. Padahal, petuah-petuah ini menggambarkan alam, baik laut maupun daratan, tidak hanya sebagai sumber daya, tetapi juga sebagai entitas suci yang harus dihormati. Tantangan utama adalah bagaimana nilai-nilai luhur ini dapat berfungsi sebagai pedoman hidup efektif dalam menjaga keseimbangan dan keselarasan lingkungan di tengah tantangan pembangunan modern, serta mencegah rusaknya hubungan harmonis antara manusia dan alam seiring berkurangnya perhatian terhadap tradisi. Metode penelitian ini adalah deskriptif kualitatif dengan pendekatan analitis, menggunakan wawancara dan studi pustaka untuk penyediaan data. Temuan menunjukkan bahwa nilai luhur lingkungan hidup merepresentasikan perwujudan kehadiran Sang Pencipta yang memelihara kelangsungan hidup masyarakat.